Language Use in Six Study Abroad Programs: An Exploratory Analysis of Possible Predictors. Issue 1 (30th December 2013) - Dewey, Dan P.; Bown, Jennifer; Baker, Wendy; Martinsen, Rob A.; Gold, Carrie; Eggett, Dennis
<x xml:space="preserve">Abstract</x> A common predictor of language gains during study abroad (SA) is amount of language use. Yet little attention has been given to determining what factors influence the extent of language use while abroad. Studies in this area have mainly been case studies of learners in single locations. In this larger study, we seek to determine variables connected with language use by examining 118 learners studying abroad in Madrid, Mérida (Mexico), Paris, Moscow, Nanjing, or Cairo. These learners reported their second language (L2) use over a 1‐week period during their stay. Significant predictors of reported L2 use include SA program, age, pre‐departure language proficiency, number of native speaker friends, gender, and personality.